Gambaran Kepatuhan Masyarakat Di Lingkungan Perumahan Rorinata Dalam Penerapan Protokol Kesehatan Di Masa Pandemi Covid-19 Medan Tahun 2020 - Imelda Derang; Maria Puji Astuti Simbolon; Lindawati Simorangkir; Rianti Lusiana S (Elisabeth Health Jurnal, 2021)
Introduction : The Covid-19 pandemic is one of the events faced by various countries in the world in the health sector and various policies have been established by the government in each country to stop the spread of the pandemic, therefore the public is required to comply with health protocols so that the spread of the Covid-19 virus does not spread. Method : This type of research is quantitative with a descriptive design. Population, all people who live in Rorinata Housing 40 KK. Sampling technique: total sampling. Result : The results showed that the obedience of the community in the Rorinata housing environment in implementing health protocols during the Covid-19 pandemic was 17 families (41.5%), non-compliant: 16 families (39.0%) and obedient: 7 families (17 , 1%), it can be concluded that most of the people in Rorinata Housing are still in the less obedient category.. Conclusion : It is hoped that the community can improve health protocols by: washing hands, using masks, maintaining social / physical distancing, and also the importance of accessing reliable sources of information about good and correct Covid-19 prevention behavior..